1981
DOI: 10.1007/bf01253095
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bromocriptine (BCT) on the on-off phenomenon

Abstract: Twenty-three patients with idiopathic Parkinson disease with classic "on-off" phenomena were studied prospectively during treatment with bromocriptine (BCT). Patients were evaluated for an average of 6 to 12 months and received an average of 56.5 mg of BCT. Nine patients (39%) showed improvement in terms of "on-off". When evaluated retrospectively, it appeared that the only difference between the responders and non-responders was a younger mean age (57.1 to 63.2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The high dose bromocriptine group consisted of 89 patients collected from five separate studies (Glantz et al, 1981;Quinn et al, 1981;Kartzinel et al, 1976 a;Kartzinel et al, 1976 b;Lieberman et al, 1976 a). The low dose bromocriptine group included 89 different patients from four separate series (Grimes et al, 1983 a;Grimes and Hassan, 1981;Fahn et al, 1980;Lieberman et al, 1976 b).…”
Section: Methodsmentioning
confidence: 99%
“…The high dose bromocriptine group consisted of 89 patients collected from five separate studies (Glantz et al, 1981;Quinn et al, 1981;Kartzinel et al, 1976 a;Kartzinel et al, 1976 b;Lieberman et al, 1976 a). The low dose bromocriptine group included 89 different patients from four separate series (Grimes et al, 1983 a;Grimes and Hassan, 1981;Fahn et al, 1980;Lieberman et al, 1976 b).…”
Section: Methodsmentioning
confidence: 99%
“…The addition of bromocriptine may also help (14). For the more unpredictable fluctuations of the proper ON/OFF phenomena, however, these manoeuvres are less frequently helpful (15). Intravenous L dopa will overcome these slumps if a constant plasma level is maintained, but this is clearly impractical (16) and hence there is significant interest in the development of slower-release preparations for oral use.…”
Section: Wearing-ofi and Onloff Phenomenamentioning
confidence: 99%
“…Bromocriptine causes more prolonged dopamine-receptor stimulation than dopamine and patients with dose-related mobility swings on levodopa may achieve a more stable response with the addition of bromocriptine (Parkes, 1979). Previous experience with bromocriptine has shown that end of dose failure (Grimes and Hassan, 1983) is improved more than the on-off phenomenon (Glantz et al, 1981). Initial experience with bromocriptine in daily fluctuations was with high doses (Parkes et al, 1976); more recently much lower doses have been shown to be effective (Teychenne et al, 1982).…”
mentioning
confidence: 99%